Strategies of finite element modeling for spot welded joints and its modal correlation with experimental data - Abdullah, N. A. Z.; Asri, M. N. A. M.; M. S. M., Sani (Penerbit Universiti Malaysia Pahang, 2022)
In building many complex engineering structures, there are many types of joining methods such as welding and fasteners that can be implemented. Modeling for joints in finite elements can be challenging as it sometimes has limiting factors that cause the prediction of the dynamic behaviour of the actual joints to be less accurate. This study aims to demonstrated several approaches of finite element modeling for spot-welded joints ad to analyse its accuracy through the correlation of modal data from experimental modal analysis. These modeling approaches are created by creating and manipulating the elements at the associated location of the spot weld joint on a top-hat beam structure. Four different approaches of spot weld modeling that uses the modeling strategies performed in other studies were created. The spot weld models are validated by comparing the modal properties of the tested structure which are obtained through finite element analysis and experiments. Model updating was performed on all models in order to observe the ability of model improvement in those different modelling approaches. The findings show that the model that uses solid elements has the lowest error compared to the model that uses beam elements. The model that uses multiple-beam elements shows the ability to be improved the most. The model that uses the simplest modeling approach using a single beam has the highest error and shows the lowest improvement after model updating. It was found that solid element is more suitable to model spot weld and the application of solid element for spot weld joints should be investigated in more types of analyses.